Sound sense : living and learning with hearing loss - Batinovich, Sara Laufer (Gallaudet University Press, 2010)
Addresses the acute need of hearing-impaired people to function at the highest level in their income-earning years. Batinovich presents step-by-step guidance in turning every challenge into an opportunity to become one's best self-advocate.